The Influence Of Compentence, Organizational Commitment, Quality Of Work Life On Organizational Citizenship Behavior In The Tourism Service Of West Java Province - Abdul Fatah; Syamsudin Syamsudin; Ratu Erlina Gentari (Journal of Management and Informatics, 2023)
This research aims to find out how big the influence is Competence, OrganizationalCommitment, Quality of Work Life on Organizational Citizenship Behavior. This research uses quantitativemethods with questionnaire data collection techniques. The population and sample in this research were 5 6employees using a saturated sampling technique method. Data collected using a questionnaire and analyzedusing SPSS V.22. Based on the research results, it can be concluded that: 1) there is an influence on theCompetency variable on organizational behavior (OCB) because t count > t table. 2) there is an influence on thevariable Organizational Commitment on Organizational Behavior (OCB) because t count > t table. 3) there is aninfluence on the Quality of Work Life variable Against organizational behavior (OCB) because t count > t table 4)there is a simultaneous positive and significant influence between Competence, Organizational Commitment,Quality of Work Life on Organizational Behavior (OCB) because f count > f table.